HUBUNGAN PENGETAHUAN DAN DUKUNGAN SUAMI TENTANG KELUARGA BERENCANA DALAM PEMILIHAN METODE KONTRASEPSI - aris noviani; Reni Puspita Sari (Jurnal Ilmiah Maternal, 2022)
ABSTRACK. Population growth can be controlled through the Family Planning program, by offering various types of contraceptive method options. The process of selecting a contraceptive device depends on a number of factors. The purpose of this study was to analyze the husband's knowledge and support about family planning in the selection of contraceptive methods. This research method is descriptive research with a cross sectional study approach, the number of respondents is 92 husbands of women of childbearing age in the working area of the Jayengan Public Health Center, Surakarta City. Data analysis using chi square test. Of the 92 respondents, the majority had poor knowledge and did not provide support in choosing a contraceptive method, as many as 39 people (69.6%) and 25 people (59.4%) who had good knowledge and provided support in choosing a contraceptive method. The results of the statistical test P = 0.000 0.05, it can be concluded (Ha) is accepted and the null hypothesis (Ho) is rejected, this indicates that there is a relationship between husband's knowledge of family planning and husband's support for family planning. choice of contraceptive method. It is recommended to disseminate information through various media about the husband's knowledge and motivation about the contraceptive method used. Keywords: support : Knowledge; Husband's support; Contraception           ABSTRAK. Pertambahan jumlah penduduk dapat dikontrol melalui program Keluarga Berencana, dengan menawarkan berbagai jenis pilihan metode kontrasepsi. Proses pemilihan kontrasepsi bergantung pada berbagai faktor. Tujuan dari penelitian ini adalah menganalisis  pengetahuan dan dukungan suami tentang KB terhadap pemilihan metode kontrasepsi. Metode penelitian ini penelitian deskriptif dengan pendekatan cross sectional study, jumlah responden sebanyak 92 suami dari wanita usia subur di wilayah kerja Puskesmas Jayengan Kota Surakarta. Analisa Data menggunakan uji chi square. Dari 92 responden, mayoritas memiliki pengetahuan kurang dan tidak memberikan dukungan dalam pemilihan metode kontrasepsi sebanyak 39 orang (69,6%) dan yang memiliki pengetahuan baik serta memberikan dukungan dalam pemilihan metode kontrasepsi sebanyak 25 orang (59,4%) . Hasil uji statistik P value = 0,0000,05 maka dapat disimpulkan (Ha) diterima dan hipotesis nol (Ho) ditolak, ini menunjukan bahwa ada hubungan antara pengetahuan suami tentang KB dan dukungan suami terhadap pemilihan metode kontrasepsi. Disarankan untuk mensosialisasikan informasi melalui berbagai media tentang pengetahuan serta motivasi suami tentang metode kontrasepsi yang digunakan. Kata kunci : Pengetahuan; Dukungan Suami; Kontrasepsi